2018
DOI: 10.1136/jim-2017-000491
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Definition of Respiratory Viral Infections in Young Children and Potential Bronchiolitis Misclassification

Abstract: Viral respiratory infections are often grouped as a single respiratory syndrome named ’viral bronchiolitis’, independently of the viral etiology or individual risk factors. Clinical trials and guidelines have used a more stringent definition of viral bronchiolitis, including only the first episode of wheezing in children less than 12 months of age without concomitant respiratory comorbidities. There is increasing evidence suggesting that this definition is not being followed by pediatric care providers, but it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
(55 reference statements)
0
16
0
3
Order By: Relevance
“…Because bronchiolitis is defined differently in the United States and in Europe, we also analyzed the data using strict (European) criteria for bronchiolitis, for example, age less than 12 months and the first wheezing episode. 1,24,25 Using these strict criteria for bronchiolitis, RV-C bronchiolitis in the first year of life was strongly associated with increased use of asthma medication 4 years later, whereas RV-A bronchiolitis was very rare in this age group. This is in agreement with our previous report on recurrence of wheezing within 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because bronchiolitis is defined differently in the United States and in Europe, we also analyzed the data using strict (European) criteria for bronchiolitis, for example, age less than 12 months and the first wheezing episode. 1,24,25 Using these strict criteria for bronchiolitis, RV-C bronchiolitis in the first year of life was strongly associated with increased use of asthma medication 4 years later, whereas RV-A bronchiolitis was very rare in this age group. This is in agreement with our previous report on recurrence of wheezing within 12-month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we identified a subgroup of 204 infants who were younger than 12 months with no history of wheezing (strict bronchiolitis criteria). 24,25 The exclusion criteria were previous enrollment or transfer to a participating hospital more than 48 hours after the original admission time. Because all the children were hospitalized, they were defined as having a severe bronchiolitis.…”
Section: Study Subjectsmentioning
confidence: 99%
“…In support of this notion, our study demonstrates that the antecedent of a single episode of severe viral LRTI is sufficient to consider these infants as a separate category from viral bronchiolitis because they have a much higher risk for subsequent recurrence (Figure 1). Clinically, early life viral respiratory infections are usually divided in those presenting for the first time versus those presenting with prior respiratory episodes of hospitalizations because these two groups of viral LRTI have different risk factors and rates of recurrence 21. Thus, the misuse of the term viral bronchiolitis in infants with a prior episode is highly inappropriate and may lead to the mistaken idea, based on clinical trials and guidelines for viral bronchiolitis,19 20 that most respiratory therapies are not clinically indicated in young children with recurrent respiratory illnesses triggered by respiratory viruses such as RV or RSV.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, we used the definition of viral bronchiolitis by the AAP in children less than 24 months of age: symptoms of a viral upper respiratory infection that then progresses to lower respiratory tract disease with wheezing and increased respiratory effort 5 . Although the European guidelines definition of bronchiolitis only include infants less than 12 months, 6 we have previously found that the AAP definition is more commonly used among young children hospitalized with viral respiratory infections 15 …”
Section: Methodsmentioning
confidence: 99%